2016
DOI: 10.1016/j.ttbdis.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Amblyomma parvum Aragão, 1908 (Acari: Ixodidae): Phylogeography and systematic considerations

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…It was considered a noteworthy result since this value of divergence among 16S rDNA sequences is similar or higher than those reported for other Neotropical taxa of Amblyomma which are considered to be different species such as Amblyomma tigrinum-Amblyomma triste-Amblyomma maculatum (Estrada-Peña et al 2005;Abarca et al 2012). Lado et al (2016) performed an extensive genetic analysis of A. parvum by using mitochondrial (the small and the large ribosomal subunits 12rDNA and 16SrDNA, the cytochrome oxidase I and II, and the control region or d-loop) and nuclear (inter transcribed spacer 2) markers. However, although Lado et al (2016) also found a separation between the populations of Argentina and Brazil with mitochondrial markers, they did not find consistently a Brazilian and an Argentinian clade separated from each other when analyses of nuclear and mitochondrial markers were undertaken integrally.…”
Section: Amblyomma Parvum Aragão 1908 Is a Hard Tick Species Widely supporting
confidence: 51%
See 2 more Smart Citations
“…It was considered a noteworthy result since this value of divergence among 16S rDNA sequences is similar or higher than those reported for other Neotropical taxa of Amblyomma which are considered to be different species such as Amblyomma tigrinum-Amblyomma triste-Amblyomma maculatum (Estrada-Peña et al 2005;Abarca et al 2012). Lado et al (2016) performed an extensive genetic analysis of A. parvum by using mitochondrial (the small and the large ribosomal subunits 12rDNA and 16SrDNA, the cytochrome oxidase I and II, and the control region or d-loop) and nuclear (inter transcribed spacer 2) markers. However, although Lado et al (2016) also found a separation between the populations of Argentina and Brazil with mitochondrial markers, they did not find consistently a Brazilian and an Argentinian clade separated from each other when analyses of nuclear and mitochondrial markers were undertaken integrally.…”
Section: Amblyomma Parvum Aragão 1908 Is a Hard Tick Species Widely supporting
confidence: 51%
“…The initial hypothesis of speciation within South American populations of A. parvum was formulated based on 16SrDNA sequence analysis (Nava et al, 2008). The speciation conjecture was, however, not totally supported when nuclear and mitochondrial DNA sequences were considered in a total evidence analysis (Lado et al, 2016). In this study, we used lines of evidence complementary to those provided by molecular markers to further test whether the splitting of the Argentinean and Brazilian lineages of A. parvum is complete or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracted DNAs were then quantified with Nanodrop 1000 (Thermo Scientific, Wilmington, DE, USA). To confirm morphological identifications, all samples were subjected to a PCR protocol amplifying a fragment of gene coding for cytochrome oxidase I subunit (COI) following Lado et al (2016). A subset of the obtained amplicons was then sequenced (i.e.…”
Section: Dna Extraction Pcr Protocols Sequence Data Analysesmentioning
confidence: 99%
“…Amblyomma parvum Aragão (Acari: Ixodidae) is a Neotropical tick species found in a range from Argentina to Mexico, and three distinct lineages can be distinguished within its broad geographic distribution (Lado et al 2016). Within its range, it is associated with dry and hot environments where adults and immature stages parasitize medium-and largesized mammals and rodents, respectively (Nava et al 2008).…”
Section: Introductionmentioning
confidence: 99%